2013
DOI: 10.1002/path.4125
|View full text |Cite
|
Sign up to set email alerts
|

Proximal tubular cells contain a phenotypically distinct, scattered cell population involved in tubular regeneration

Abstract: Regeneration of injured tubular cells occurs after acute tubular necrosis primarily from intrinsic renal cells. This may occur from a pre-existing intratubular stem/progenitor cell population or from any surviving proximal tubular cell. In this study, we characterize a CD24-, CD133-, and vimentin-positive subpopulation of cells scattered throughout the proximal tubule in normal human kidney. Compared to adjacent ‘normal’ proximal tubular cells, these CD24-positive cells contained less cytoplasm, fewer mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
246
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 206 publications
(275 citation statements)
references
References 34 publications
23
246
0
6
Order By: Relevance
“…Our first major finding is that the inducible PEC-rtTA transgenic mouse labels STCs besides PECs but not other adjacent epithelial cells (i.e., podocytes or all remaining proximal tubular cells). This is consistent with previous proposals and data (12,15,17) that STCs express almost the same marker proteins as PECs, which are not shared by normal tubular cells in human kidney, suggesting a common transcriptional program in STCs and PECs. More than 80% of KIM-1-positive proximal tubular cells were also labeled by the PEC-rtTA mouse, and these cells consistently showed a higher proliferative index in vivo, which are characteristic features of STCs (11,12,17).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our first major finding is that the inducible PEC-rtTA transgenic mouse labels STCs besides PECs but not other adjacent epithelial cells (i.e., podocytes or all remaining proximal tubular cells). This is consistent with previous proposals and data (12,15,17) that STCs express almost the same marker proteins as PECs, which are not shared by normal tubular cells in human kidney, suggesting a common transcriptional program in STCs and PECs. More than 80% of KIM-1-positive proximal tubular cells were also labeled by the PEC-rtTA mouse, and these cells consistently showed a higher proliferative index in vivo, which are characteristic features of STCs (11,12,17).…”
Section: Discussionsupporting
confidence: 82%
“…We later confirmed that nearly all marker proteins (45 of 49) that we found to be expressed by STCs were also expressed by PECs (12). This finding triggered us to use our Significance Acute kidney injury (AKI) is a common and significant clinical problem for which no specific therapy has been developed.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…Second, in a previous study we detected ANXA3 in a specific population of proximal tubular cells of the kidney, the so-called scattered tubular cells. 19,20 Scattered tubular cells express similar proteins as PECs. In the present study, we found that within the glomerulus ANXA3 was expressed exclusively by PECs and infiltrating leukocytes 21 ( Figure 7D).…”
Section: Detecting Pecs In Sclerotic Lesions By Using Akap12 or Anxa3mentioning
confidence: 99%